Dampak Infrastruktur Objek Wisata Burake Terhadap Pertumbuhan Ekonomi Lokal - Maryones Lino’ Tangdiembong; Olivia Devi Y. Pompeng; Marchelin Marchelin (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research aims to determine the impact of the infrastructure of the Burake Tourist Attraction on the economic growth of the community around the Burake Tourist Attraction. The research method used in this research is qualitative research. Data was collected through interview and observation procedures. The informants for this research consisted of 7 people consisting of 2 local people, 2 people who were business actors at the Burake Tourist Attraction, 1 levy collector at the Burake Tourist Attraction, 1 tourism service employee, and 1 tourist. The research results show that the existence of the Burake tourist attraction has an impact on the economic growth of the local community and has a good influence on the development of infrastructure such as roads and electricity. The development of infrastructure supports and makes it easier for people who are business actors at the Burake Tourist Attraction, especially road infrastructure, making accessibility easier for both local people and tourists. Indirectly, the existence of the Burake Tourist Attraction which is supported by adequate infrastructure can help the economic growth of the community around the Burake Tourist Attraction. This economic growth includes creating jobs, increasing income and opening up business opportunities.